On the modelling of strength differential and anisotropy exhibited by titanium. Issue 3 (August 2016) - Manopulo, Niko; Raemy, Christian; Hora, Pavel
Abstract: Modelling the response of titanium alloys under plastic deformation is challenging. In addition to strong anisotropy, these materials exhibit tension-compression asymmetry as well as anisotropic hardening even under monotonous loading conditions. The present contribution aims to propose a new modelling approach for titanium materials, by a homogeneous introduction of asymmetry into existing symmetric yield functions. Furthermore, anisotropic hardening effects are tracked describing the strain dependant yield surface evolution. The results are validated using the earing profile of deep drawn cups.